Preservation of indigenous culture and tradition through tourism: a study on mah meri community in Carey Island, Malaysia - Abd Hamid, Zuliah; Mohd Anuar, Nor Asmalina; Ahmad, Khairun Najiah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
To support sustainable tourism practices in the Malaysian tourism context, this study is regarded as an exploratory study that focuses on the development of cultural tourism in the Mah Meri Community, which includes both tangible and intangible cultural heritage. The focus is on the identity, preservation of the cultural heritage, and promotion of cultural products of the Mah Meri Community, a local Orang Asli community on Carey Island in Selangor, Malaysia. The research's overarching goal is to investigate the factors in the preservation of the cultural features of the Mah Meri Community as a tourism product that can help in promoting the destinations to other people from different backgrounds, races, destinations, and customs. The qualitative data collection helped the researcher to holistically understand the community's cultural identity, characteristics, and resources in the form of cultural tourism products. However, the local community believes that their identity as a potential tourist draw is increasingly threatened due to a lack of natural resources and the government's attention.